Perception of college students on civic and anti-corruption education: Importance and relevance - Zulqarnain Zulqarnain; Muhammad Ikhlas; Rosita Ilhami (Integritas: Jurnal Antikorupsi, 2022)
Corruption is an extraordinary crime that requires extra effort to deal with. KPK takes extra steps in dealing with corrupt behavior, namely by taking preventive actions through educational institutions. In higher education, KPK collaborates with related stakeholders to implement anti-corruption education for college students. This study explores the initial perception of college students toward civic and anti-corruption education. Qualitative with a case study approach has been used as the method of this study. The findings show that the majority of college students perceive that civic and anti-corruption education is very important to study and relevant to the condition of the nation currently.